Multilevel obstacles to heart-healthy living in the context of Ischemic heart disease: A qualitative study - Bardia Amidi; Narges Naderi; Javad Yoosefi Lebni; Arash Amin (PLoS ONE, 2025)
Background Ischemic heart disease (IHD) is a major contributor to global morbidity and mortality. Lifestyle modifications play a central role in preventing and management of IHD, yet patients face barriers to engaging in healthy behaviors. This study explored these barriers among IHD patients in Lorestan Province, Iran. Methods A qualitative study using conventional content analysis was conducted. Semi-structured interviews were held with 31 IHD patients and 8 key informants (3 cardiologists, 2 cardiology residents, and 3 ward nurses), selected through purposive sampling. Data were analyzed using MAXQDA-2020 based on the Granheim and Lundman approach. Guba and Lincoln’s criteria were applied to ensure trustworthiness. Results Data analysis led to the identification of four main categories, 17 subcategories, and 413 primary codes. The categories identified included socio-cultural barriers, such as taboos surrounding women’s sports, misconceptions about sports, fatalism, unhealthy dietary patterns and beliefs, and patterns and beliefs regarding the use of addictive substances. Economic barriers included the economic crisis and the high cost of a healthy lifestyle. Individual barriers included a lack of prioritization of personal health, unhealthy food preferences, lack of access to facilities and conditions for a healthy lifestyle, personality traits, and low health literacy. Healthcare-medical barriers included communication challenges in healthcare, management and infrastructure challenges in healthcare services, gaps in patient education and healthcare delivery, and the perceived insignificance of lifestyle recommendations by patients. These interrelated barriers highlight the compounded difficulties IHD patients face in adopting and sustaining a healthy lifestyle. Conclusion This study identified multifaceted lifestyle modification barriers in IHD patients including sociocultural, economic, individual, and healthcare system factors. These necessitate community-based intervention, financial support for healthy living, tailored education, and health system reform to include systematic lifestyle counseling in regular care. Future studies are needed to evaluate the feasibility of these interventions to improve long-term health outcomes in IHD patients.